Pseudorotaxane supermolecular network binder, silicon negative electrode sheet, battery and preparation method

CN122978918APending Publication Date: 2026-10-27DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611158163.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本申请提供一种准轮烷超分子网络粘结剂、硅负极极片、电池及制备方法,以解决相关技术中硅负极粘结剂在充放电循环过程中因化学交联键不可逆断裂导致局部应力集中且无法有效释放,进而导致电极结构崩塌、界面阻抗上升、容量快速衰减的问题

Benefits of technology

本申请实施例提供了一种准轮烷超分子网络粘结剂、硅负极极片、电池及制备方法,本实施例中,构建包含轴分子、穿套于轴分子的环状分子及封端物质的准轮烷结构单元,并利用轴分子侧链的第一官能团与环状分子侧链的第二官能团形成的非共价键连接准轮烷结构单元构成三维超分子网络,借助非共价穿套的环状分子沿轴分子自由滑移的应力诱导滑移机制配合非共价键的可逆断裂与重组特性,实现网络节点在应力作用下的解离与重组,实现全局应力的重新分布与释放,解决了相关技术中硅负极粘结剂在充放电循环过程中因化学交联键不可逆断裂导致局部应力集中且无法有效释放,进而导致电极结构崩塌、界面阻抗上升、容量快速衰减的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978918A_ABST
    Figure CN122978918A_ABST
Patent Text Reader

Abstract

The application relates to a quasi-wheel-alternating supermolecular network binder, a silicon negative electrode sheet, a battery and a preparation method, wherein the quasi-wheel-alternating supermolecular network binder comprises quasi-wheel-alternating structural units, the quasi-wheel-alternating structural units comprise a shaft molecule, a ring-shaped molecule sleeved on the shaft molecule and end-capping substances connected to both ends of the shaft molecule; the side chain of the shaft molecule contains a first functional group capable of forming a hydrogen bond; the side chain of the ring-shaped molecule contains a second functional group capable of forming a hydrogen bond; and non-covalent bonds formed between each quasi-wheel-alternating structural unit through the first functional group and / or the second functional group constitute a three-dimensional supermolecular network. The application can solve the problem that, in the related art, the chemical cross-linking bond of a silicon negative electrode binder is irreversibly broken during a charge-discharge cycle process, local stress concentration cannot be effectively released, and then electrode structure collapse, interface impedance rise and capacity rapid decay problems are caused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a quasi-rotaxane supramolecular network binder, a silicon anode sheet, a battery, and a preparation method thereof. Background Technology

[0002] Silicon-based anodes offer numerous advantages as anodes in high-energy-density solid-state batteries, such as a theoretical specific capacity at room temperature that is ten times that of traditional graphite anodes, a low delithiation site, environmental friendliness, and good chemical stability. However, the significant volume expansion of silicon anodes after lithium intercalation is a major challenge in their application.

[0003] The lithium storage mechanism of silicon-based anodes involves an alloying reaction, which leads to severe volume expansion, causing the material to gradually fracture and pulverize. Furthermore, the repeated formation of the SEI film results in irreversible loss of active lithium and rapid capacity decay. These problems ultimately reduce the coulombic efficiency and cycle life of silicon-based lithium-ion batteries.

[0004] One of the most effective methods to suppress the expansion of silicon-based anodes is to use binders to maintain the contact integrity between active materials, conductive additives and current collectors, reduce the cracking and pulverization caused by volume changes in silicon materials during charge and discharge cycles, maintain the high capacity of silicon anodes, and improve battery cycle performance.

[0005] Currently, adhesives mainly utilize linear or slightly cross-linked polymers, such as polyacrylic acid (PAA), sodium alginate (SA), and sodium carboxymethyl cellulose (CMC). These adhesives form hydrogen bonds with the oxide layer (Si-OH) on the surface of silicon particles through functional groups such as carboxyl and hydroxyl groups on their molecular chains, thereby achieving adhesion between particles and between particles and current collectors. Some technologies further introduce chemical cross-linking agents (such as glutaraldehyde, epoxy resin, and boric acid) to form a covalent cross-linked network between the adhesive molecular chains, thereby enhancing bonding strength and structural stability.

[0006] However, the volume expansion of the silicon anode renders the linear binder ineffective in constraining particle displacement, leading to electrode structure collapse and electrical contact failure. While introducing chemical crosslinking improves initial bond strength, the covalent crosslinking points are irreversible. During repeated cycles of large volume expansion and contraction, the crosslinks are stretched to break and cannot recover, resulting in gradual network failure, a sharp increase in interfacial impedance, and rapid capacity decay. This is because there is a lack of stress release mechanism; all stress is concentrated on the chemical bonds. Summary of the Invention

[0007] This application provides a quasi-rotaxane supramolecular network binder, a silicon anode sheet, a battery, and a preparation method to solve the problem in related technologies where the silicon anode binder suffers from localized stress concentration and ineffective release due to irreversible breakage of chemical crosslinking bonds during charge-discharge cycles, leading to electrode structure collapse, increased interfacial impedance, and rapid capacity decay.

[0008] In a first aspect, embodiments of this application provide a quasi-rotaxane supramolecular network binder, the quasi-rotaxane supramolecular network binder comprising quasi-rotaxane structural units, the quasi-rotaxane structural units comprising an axonal molecule, a cyclic molecule sleeved on the axonal molecule, and end-capping substances connected to both ends of the axonal molecule; The side chains of the axial molecule contain a first functional group capable of forming hydrogen bonds; The side chains of the cyclic molecule contain a second functional group capable of forming hydrogen bonds; The quasi-rotaxane structural units form a three-dimensional supramolecular network through non-covalent bonds formed by the first functional group and / or the second functional group.

[0009] In conjunction with the first aspect, in one embodiment, the axial molecule is a linear polymer, and the number-average molecular weight of the linear polymer is 50,000 to 500,000. And / or, the first functional group includes at least one of carboxyl, hydroxyl and amino groups; And / or, the axial molecule includes at least one of acrylic acid, sodium alginate, sodium carboxymethyl cellulose, guar gum, polyethylene glycol, polyvinyl alcohol, chitosan, polyvinylamine, polyallylamine, and gelatin.

[0010] In conjunction with the first aspect, in one embodiment, the cyclic molecule includes at least one selected from α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, carboxycucurbita, and carboxy crown ether; And / or, the second functional group includes at least one of carboxyl and hydroxyl groups.

[0011] In conjunction with the first aspect, in one embodiment, the quasi-rotaxane supramolecular network binder further includes divalent or higher metal ions, which form ionic bonds with the first functional groups on the side chains of the axonal molecules to connect the axonal molecules of different quasi-rotaxane structural units; And / or, the end-capping material includes at least one of nano-silica, nano-diamond, dendritic macromolecules, fullerene, 2,4-dinitrofluorobenzene and protein; And / or, the molar ratio of the cyclic molecule to the axial molecule is 1:(10-100). And / or, the molar ratio of the end-capping material to the axial molecule is (1-3):1.

[0012] Secondly, embodiments of this application provide a method for preparing a quasi-rotaxane supramolecular network binder as described above, comprising: Dissolve the axial molecules in the first solvent to obtain an axial molecule solution; A cyclic molecule is added to the axial molecule solution to perform cyclization, thereby obtaining a quasi-rotaxane intermediate solution; An end-capping substance was added to the quasi-rotaxane intermediate solution to carry out an end-capping reaction, resulting in a reaction solution. The reaction solution was purified to obtain a quasi-rotaxane supramolecular network binder.

[0013] In conjunction with the second aspect, in one embodiment, the end-capping reaction includes: stirring the reaction at 40–60°C for 12–24 hours; And / or, the piercing process includes: ultrasonication for 1 to 6 hours at a power of 100 to 300 W.

[0014] Thirdly, embodiments of this application provide a silicon anode sheet, which includes an active material, a conductive agent, and a quasi-rotaxane supramolecular network binder as described above.

[0015] In conjunction with the third aspect, in one embodiment, the mass ratio of the quasi-rotaxane supramolecular network binder, the active substance, and the conductive agent is (5-15):(70-90):(5-15). And / or, the particle size of the active substance is 50-150 nm.

[0016] Fourthly, embodiments of this application provide a method for preparing the silicon negative electrode sheet as described above, comprising: After mixing the quasi-rotaxane supramolecular network binder, active material and conductive agent, a second solvent is added to prepare a silicon anode slurry; The silicon anode slurry is coated onto the current collector and dried to obtain a silicon anode sheet.

[0017] Fifthly, embodiments of this application provide a battery comprising the silicon negative electrode sheet as described above.

[0018] The beneficial effects of the technical solution provided in this application include: This application provides a quasi-rotaxane supramolecular network binder, a silicon anode electrode, a battery, and a preparation method. In this embodiment, a quasi-rotaxane structural unit is constructed, comprising an axonal molecule, a cyclic molecule encased within the axonal molecule, and a capping material. The quasi-rotaxane structural unit is connected by non-covalent bonds formed by the first functional group of the axonal molecule's side chain and the second functional group of the cyclic molecule's side chain to form a three-dimensional supramolecular network. By utilizing the stress-induced slip mechanism of the non-covalently encased cyclic molecule freely sliding along the axonal molecule, combined with the reversible breaking and recombination characteristics of the non-covalent bonds, the network nodes can be dissociated and recombined under stress, achieving a redistribution and release of global stress. This solves the problem in related technologies where the irreversible breakage of chemical crosslinking bonds during charge-discharge cycles leads to local stress concentration and ineffective release, resulting in electrode structure collapse, increased interfacial impedance, and rapid capacity decay. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 A flowchart illustrating the preparation method of the quasi-rotaxane supramolecular network binder provided in the embodiments of this application. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0022] This application provides a quasi-rotaxane supramolecular network binder, which includes quasi-rotaxane structural units. Each quasi-rotaxane structural unit comprises an axis molecule, a cyclic molecule encased within the axis molecule, and end-capping materials connecting both ends of the axis molecule. The quasi-rotaxane structural unit employs a non-covalent encasing structure; specifically, there are no covalent bonds between the cyclic molecule and the axis molecule; they encase each other only through physical interaction and are confined by the end-capping materials, thereby enabling the cyclic molecule to freely slide along the axis molecule on a large scale. When the silicon anode expands in volume, the stress-induced slippage of the cyclic molecules transforms the local stress generated by silicon expansion into global stress, achieving stress redistribution rather than relying on the stretching or breaking of chemical bonds to bear the stress.

[0023] The side chains of the axial molecule contain a first functional group capable of forming hydrogen bonds; the side chains of the cyclic molecule contain a second functional group capable of forming hydrogen bonds; and the quasi-rotaxane structural units form a three-dimensional supramolecular network through non-covalent bonds formed by the first functional group and / or the second functional group.

[0024] The three-dimensional supramolecular network is a physically dynamic network. The three-dimensional network of the binder is entirely constructed by non-covalent interactions, and has reversible breaking and recombination characteristics, avoiding the irreversible failure of chemical cross-linking bonds.

[0025] In this embodiment, a quasi-rotaxane structural unit is constructed, comprising an axonal molecule, a cyclic molecule encasing the axonal molecule, and a capping material. The quasi-rotaxane structural unit is connected by non-covalent bonds formed by the first functional group of the axonal molecule's side chain and the second functional group of the cyclic molecule's side chain to form a three-dimensional supramolecular network. Utilizing the stress-induced slip mechanism of the non-covalently encased cyclic molecule freely sliding along the axonal molecule, combined with the reversible breaking and recombination characteristics of the non-covalent bonds, the network nodes can dissociate and recombine under stress, achieving a redistribution and release of global stress. This solves the problem in related technologies where irreversible breakage of chemical crosslinking bonds in silicon anode binders during charge-discharge cycles leads to localized stress concentration and ineffective stress release, resulting in electrode structure collapse, increased interfacial impedance, and rapid capacity decay.

[0026] Further, in one embodiment, the axial molecule is a linear polymer with a number-average molecular weight of 50,000 to 500,000. Further, in one embodiment, the first functional group includes at least one of carboxyl, hydroxyl, and amino groups. The axial molecule includes at least one of acrylic acid, sodium alginate, sodium carboxymethyl cellulose, guar gum, polyethylene glycol, polyvinyl alcohol, chitosan, polyvinylamine, polyallylamine, and gelatin.

[0027] For example, acrylic acid contains carboxyl groups; sodium alginate contains carboxyl and hydroxyl groups; sodium carboxymethyl cellulose contains carboxyl and hydroxyl groups; guar gum contains hydroxyl groups; polyethylene glycol contains hydroxyl groups; polyvinyl alcohol contains hydroxyl groups; chitosan contains hydroxyl and amino groups; polyvinylamine contains amino groups; polyallylamine contains amino groups; and gelatin contains carboxyl, hydroxyl, and amino groups.

[0028] Further, in one embodiment, the second functional group includes at least one of carboxyl and hydroxyl groups, and the cyclic molecule includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, carboxycucurbita, and carboxy crown ether.

[0029] For example, α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin contain hydroxyl groups; carboxylated cucurbituril contains a carboxyl group; and carboxylated crown ethers contain a carboxyl group.

[0030] It should be noted that the hydrogen bond formation mechanism is based on the electrostatic attraction between the hydrogen bond donor and the hydrogen bond acceptor. In this embodiment, the carboxyl, hydroxyl, or amino groups selected for the first and second functional groups all contain electronegative atoms (such as oxygen and nitrogen) and their attached hydrogen atoms, as well as lone pairs of electrons in their molecular structures. Based on this, the hydrogen bonds formed between the first and second functional groups can be formed through interactions between similar functional groups and interactions between dissimilar functional groups. In the case of interactions between similar functional groups, for example, between two carboxyl groups, one carboxyl group provides a hydroxyl hydrogen as a donor, and the other carboxyl group provides a carbonyl oxygen as an acceptor, forming a stable dimer structure; for hydroxyl groups, hydrogen bonds can also be formed through the coordination of oxygen and hydrogen atoms. This multiple hydrogen bond interaction based on the donor and acceptor sites within the functional group provides effective connectivity between quasi-rotaxane structural units, supporting the self-assembly of the three-dimensional supramolecular network.

[0031] Furthermore, in one embodiment, the end-capping material is an organic macromolecule or inorganic nanoparticle with a volume larger than the cavity of the cyclic molecule. For example, the end-capping material includes at least one of nano-silica, nano-diamond, dendritic macromolecule, fullerene, 2,4-dinitrofluorobenzene, and protein. The end-capping material is covalently or electrostatically connected to both ends of the axial molecule to prevent the cyclic molecule from slipping off.

[0032] As an example, the dendritic molecules can be polyamide-amine dendritic molecules (PAMAM) or polypropylene imine dendritic molecules (PPI). The proteins can be bovine serum albumin (BSA) or gelatin.

[0033] Furthermore, in one embodiment, the quasi-rotaxane supramolecular network binder further includes divalent or higher-valent metal ions, which form ionic bonds with the first functional groups on the axonal molecular side chains to connect the axonal molecules of different quasi-rotaxane structural units. The metal ions are selected from Zn. 2+ Ca 2+ Mg 2+ wait.

[0034] It should be noted that the purpose of introducing metal ions in this embodiment is to further enhance the mechanical strength of the three-dimensional supramolecular network through ionic coordination. Specifically, the first functional group of the axonal molecular side chain is preferably a carboxyl group, which can dissociate into a carboxylate anion in solution. Divalent and higher-valent metal ions have multiple coordination sites and can simultaneously form ionic bonds with carboxylate anions on two or more different axonal molecules, thereby constructing ionic bond crosslinking points between adjacent quasi-rotaxane structural units, acting as "ionic bridges." Through this ionic bond crosslinking, not only is the overall strength of the network improved, but also, due to the dynamic reversibility of ionic bonds, the network retains its stress release capability. In the actual preparation process, the formed quasi-rotaxane supramolecular network binder can be immersed in a salt solution containing divalent and higher-valent metal ions, allowing the metal ions to diffuse into the network and undergo coordination reactions with the first functional group.

[0035] In this embodiment, by introducing divalent or higher metal ions to form ionic bonds with the first functional group on the side chain of the axon molecules, different axon molecules are connected. The reversible coordination characteristics of ionic bonds are used to enhance the network strength and realize dynamic stress release, thus solving the problems of electrode structure collapse and capacity decay in related technologies.

[0036] Furthermore, in one embodiment, the molar ratio of the cyclic molecule to the axial molecule is 1:(10-100).

[0037] It should be noted that the molar ratio of cyclic molecules to axial molecules affects the entanglement density and stress-induced slip effect of the quasi-rotaxane structural unit. If the ratio is lower than 1:100, the number of cyclic molecules entangled on the axial molecules is insufficient, making it difficult to form an effective slip network and resulting in weak stress dispersion. If the ratio is higher than 1:10, the cyclic molecules are arranged too tightly on the axial molecules, producing a steric hindrance effect that restricts the free slip of the cyclic molecules, thus reducing the stress release effect. This embodiment selects a range of 1:(10-100), which can ensure sufficient entanglement density to construct a three-dimensional network while reserving sufficient slip space for the cyclic molecules, thereby optimizing the mechanical properties and self-healing ability of the binder.

[0038] Furthermore, in one embodiment, the molar ratio of the end-capping material to the axial molecules is (1-3):1.

[0039] As an example, dendritic end-capping agents such as PAMAM and PPI are preferably used in a ratio of (1-3):1 because the surface of the dendritic macromolecule contains multiple reaction sites (e.g., PAMAM G2 contains 8 amino groups, and G4 contains 32 amino groups). A single dendritic macromolecule can react with the ends of the axon molecules.

[0040] As an example, protein capping agents such as bovine serum albumin (BSA) and gelatin are preferred in a ratio of (1-3):1, because proteins have large molecular weights and contain multiple amino / carboxyl groups on their surface, so a single protein molecule can be capped.

[0041] Further, see Figure 1 As shown in the embodiments of this application, a method for preparing a quasi-rotaxane supramolecular network binder is also provided, which includes: S101: Dissolve the axial molecules in the first solvent to obtain an axial molecule solution.

[0042] In this step, the first solvent is a polar organic solvent such as ethanol, propanol, or deionized water. The interaction between the solvent molecules and the functional groups of the side chains of the axon molecules breaks the intermolecular forces, allowing them to fully expand and disperse in the solvent, forming a uniform and stable axon molecule solution. This provides a uniform liquid-phase reaction environment for the subsequent ring-crossing reaction, ensuring the ring-crossing efficiency.

[0043] S102: Add cyclic molecules to the axial molecule solution to perform circumcircle-crossing and obtain a quasi-rotaxane intermediate solution.

[0044] The piercing process includes: ultrasonic treatment at a power of 100-300W for 1-6 hours.

[0045] In this step, the energy provided by ultrasonic cavitation overcomes the steric hindrance during the cyclic molecule's slip-through process, causing the cyclic molecule to slide along the axial molecular chain and complete the slip-through. By controlling the reaction time and power, the cyclic molecule slips onto the axial molecule at a specific molar ratio, forming a quasi-rotaxane intermediate with slip potential, laying the structural foundation for constructing a stress-induced slip network.

[0046] S103: Add a capping substance to the quasi-rotaxane intermediate solution to carry out a capping reaction and obtain a reaction solution.

[0047] The end-capping reaction includes stirring the reaction at 40–60°C for 12–24 hours.

[0048] In this step, the end-capping material has a volume larger than the cavity of the cyclic molecule and is connected to both ends of the axon molecule via covalent bonds or electrostatic interactions, forming a physical steric barrier to prevent the already capped cyclic molecule from slipping off the ends of the axon molecule. This step locks in the quasi-rotaxane topology, ensuring that the cyclic molecule can only slide freely within the range confined by the axon molecule under subsequent stress, thus maintaining structural stability.

[0049] S104: The reaction solution is purified to obtain a quasi-rotaxane supramolecular network binder.

[0050] In this step, unreacted free cyclic molecules, end-capping substances, and solvent impurities in the reaction solution are removed by dialysis or precipitation to prevent these impurities from interfering with the subsequent formation of the supramolecular network. After drying, a pure quasi-rotaxane supramolecular network binder solid is obtained, ensuring the content of effective structural units in the binder and guaranteeing its expected stress release and bonding performance in the silicon anode electrode.

[0051] The working principle of the quasi-rotaxane supramolecular network binder prepared in this application is as follows: During battery charging and discharging, silicon particles undergo volume expansion, and the resulting stress is transferred to the three-dimensional supramolecular network through strong hydrogen bonds between the side chains of the axial molecules and the silicon surface. At this time, the ring molecules encased on the axial axis can slide freely along the axis, converting localized stress concentration into long-range sliding motion of the ring molecules, thereby achieving global stress redistribution and release. When the silicon particles contract, the ring molecules partially slide back to their original position under thermodynamic drive. Throughout this process, physical cross-linking points (hydrogen bonds, ionic bonds) reversibly break and recombine, consuming additional energy and avoiding irreversible destruction of chemical bonds. Due to the intact electrode structure and the absence of continuous conductive network collapse, the charge transfer impedance (Rct) increases slowly after cycling, resulting in excellent rate performance. The electrode surface roughness changes little and the local modulus distribution is uniform after cycling.

[0052] The preparation process in this embodiment is simple and cost-controllable. It does not require complex covalent grafting or multi-step organic synthesis. The quasi-rotaxane structure can be obtained simply by ultrasonic mixing and physical end-capping, making it suitable for large-scale production.

[0053] Furthermore, the method for introducing metal ions is as follows: Step 1: Preparation of quasi-rotaxane solution The purified quasi-rotaxane supramolecular network binder was redissolved in deionized water to prepare a binder stock solution with a certain solid content. Stirring was continued until completely dissolved; if necessary, slight heating (40–50°C) could be applied to promote dissolution.

[0054] Step 2: Preparation and introduction of metal ion salt solution Metal ion salts (such as sulfates, nitrates, chlorides, etc.) are dissolved in deionized water to prepare a salt solution with a concentration of 0.1–0.5 mol / L. Under stirring conditions (stirring time 30 min–4 h, stirring speed 200–600 rpm, avoiding excessive speed to prevent bubble generation), the metal ion salt solution is slowly added dropwise to the quasi-rotaxane solution. Stirring continues to allow the metal ions to fully coordinate with the first functional group of the axial molecular side chain, such as the carboxyl group, to form ionic cross-linking points.

[0055] To avoid uneven gelation due to excessively high local concentrations, the salt solution should be added slowly by dripping rather than being poured out all at once.

[0056] The molar ratio of metal ions to the first functional group is 1:(4-8). If the ratio is too low (e.g., <1:10), the cross-linking will be insufficient and the network reinforcement effect will be insignificant. If the ratio is too high (e.g., >1:2), the cross-linking will be too dense, the binder will become brittle, and the slurry viscosity will be too high, affecting the coating processability.

[0057] Furthermore, embodiments of this application also provide a silicon negative electrode sheet, which includes an active material, a conductive agent, and a quasi-rotaxane supramolecular network binder.

[0058] It should be noted that the active material is selected from at least one of nano-silicon particles, silicon suboxide, and silicon-carbon composite materials, and the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes, graphene, or graphite.

[0059] The mass ratio of the quasi-rotaxane supramolecular network binder, active material and conductive agent is (5-15):(70-90):(5-15).

[0060] The particle size of the active substance is 50–150 nm.

[0061] Furthermore, embodiments of this application also provide a method for preparing a silicon negative electrode sheet, which includes: S201: After mixing the quasi-rotaxane supramolecular network binder, active material and conductive agent, a second solvent is added to prepare the silicon anode slurry.

[0062] In this step, the quasi-rotaxane supramolecular network binder, active material, and conductive agent are mixed and stirred in a solvent to ensure uniform dispersion of the components and form a silicon anode slurry. Uniform mixing helps the binder encapsulate the active material, establishes a conductive network, provides uniformity for subsequent coating, and prevents slurry delamination from affecting electrode performance.

[0063] The solid content of the prepared silicon anode slurry can be limited to 15-25 wt%, and it can also undergo vacuum degassing treatment.

[0064] The second solvent can be deionized water or distilled water, etc.

[0065] S202: The silicon anode slurry is coated onto the current collector and dried to obtain a silicon anode sheet.

[0066] In this step, the silicon anode slurry is uniformly coated onto the surface of the current collector and vacuum dried at 60–80°C for 12 hours. The drying process removes the solvent and allows the binder to solidify into a film. Drying promotes close contact between the binder and the active material, allowing them to adhere to the current collector and form a structurally stable silicon anode sheet, ensuring that the sheet has good mechanical strength and electrochemical activity.

[0067] Furthermore, embodiments of this application also provide a battery comprising the aforementioned silicon negative electrode sheet.

[0068] It should be noted that the battery may be a lithium-ion battery, a lithium metal battery, or a solid-state battery.

[0069] The present application will be described below through some specific embodiments.

[0070] Example 1 Step (1): Adhesive preparation The adhesive preparation method is as follows: Sodium alginate with axial molecular weight is dissolved in deionized water to obtain an axial molecular weight solution; Cyclic molecule α-cyclodextrin was added to the axial molecule solution, and the mixture was sonicated at 200W for 2 hours to perform cyclization, thereby obtaining a quasi-rotaxane intermediate solution, wherein the molar ratio of the cyclic molecule to the axial molecule was 1:20. Nano-silica, a capping material, was added to the quasi-rotaxane intermediate solution, and the mixture was stirred at 50°C for 18 hours to obtain a reaction solution. The molar ratio of the capping material to the axial molecules was 3:1. The reaction solution was purified to obtain a quasi-rotaxane supramolecular network binder.

[0071] (2) Preparation of silicon negative electrode sheet: The method for preparing silicon anode plates is as follows: the binder prepared in step (1) is mixed with nano-silicon particles and conductive carbon black in a mass ratio of 9:85:6, and then deionized water is added to prepare silicon anode slurry. The silicon anode slurry is coated onto the current collector and dried under vacuum at 60°C for 12 hours to obtain a silicon anode sheet.

[0072] Example 2 The difference between this embodiment and Example 1 is that: the axial molecule is chitosan, the cyclic molecule is β-cyclodextrin, the end-capping substance is PAMAM G2, the molar ratio of the cyclic molecule to the axial molecule is 1:10, the molar ratio of the end-capping substance to the axial molecule is 2:1, the reaction is carried out by sonication at 150W for 3 hours to perform circumduction, and the reaction is stirred at 40°C for 24 hours to obtain the reaction solution.

[0073] Example 3 The difference between this embodiment and Example 1 is that: the axial molecule is polyethylene glycol, the cyclic molecule is γ-cyclodextrin, the end-capping substance is 2,4-dinitrofluorobenzene, the molar ratio of the cyclic molecule to the axial molecule is 1:25, the molar ratio of the end-capping substance to the axial molecule is 1:1, the reaction is carried out by sonication at 300W for 1 hour to perform circumduction, and the reaction is stirred at 60°C for 12 hours to obtain the reaction solution.

[0074] Example 4 The difference between this embodiment and Example 1 is that: the axial molecule is polyethyleneamine, the cyclic molecule is carboxymethyl-β-cyclodextrin, the end-capping material is BSA, the molar ratio of the cyclic molecule to the axial molecule is 1:10, the molar ratio of the end-capping material to the axial molecule is 2:1, the reaction is carried out by sonication at 250W for 4 hours to perform circumduction, and the reaction is stirred at 45°C for 20 hours to obtain the reaction solution.

[0075] Example 5 The difference between this embodiment and Example 1 is that: sodium alginate is used as the axial molecule, α-cyclodextrin is used as the cyclic molecule, gelatin is used as the end-capping material, the molar ratio of the cyclic molecule to the axial molecule is 1:10, the molar ratio of the end-capping material to the axial molecule is 2:1, the reaction is carried out by sonication at 200W for 2 hours to perform circumduction, and the reaction is stirred at 40°C for 24 hours to obtain the reaction solution.

[0076] Example 6 The difference between this embodiment and Embodiment 1 is that the metal ion Zn is introduced. 2+ The molar ratio of metal ions to the first functional group on sodium alginate is 1:6.

[0077] Comparative Example 1 The difference between this comparative example and Example 1 is that CMC is used instead of the quasi-rotaxane supramolecular network binder.

[0078] The silicon anode sheets prepared in Examples 1 to 6 and Comparative Example 1 were used to assemble coin cells and their performance was tested.

[0079] 1) The method for assembling a button cell is as follows: The assembly process in the glove box is as follows: place the positive electrode shell (CR2032) → place the gasket → place the negative electrode sheet (12mm in diameter) → place 30μL of electrolyte → place the separator (19mm in diameter) → place 30μL of electrolyte → place the lithium sheet (15.6mm in diameter) → place the gasket → place the spring sheet → place the negative electrode shell → compact to obtain a button half-cell.

[0080] 2) Battery testing methods: Install the battery on the button cell test cabinet and set it to 0.1C / 0.1C for two weeks to activate the battery. At this time, the coulombic efficiency of the battery in the first week can be read on the device. Then, use 0.5C / (0.2C-0.1C) to run the cycle and read the capacity retention rate of the battery at the 100th and 200th cycles respectively.

[0081] The test results are shown in Table 1 below: Table 1 Test Results

[0082] Table 1 shows that the first-cycle coulombic efficiency of Examples 1-6 is superior to that of the comparative example. Simultaneously, the cycle performance is significantly improved. The 100-cycle retention rate of Examples 1-6 is 84%-93%, far exceeding the 74% of the comparative example; the 200-cycle retention rate is 72%-85%, approximately 1.8 times that of the comparative example (47%). This indicates that the quasi-rotaxane binder of this application can effectively alleviate the volume expansion of the silicon anode and extend the battery cycle life, which is superior to traditional CMC.

[0083] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A quasi-rotaxane supramolecular network binder, characterized in that: The quasi-rotaxane supramolecular network binder includes quasi-rotaxane structural units, each of which includes an axial molecule, a cyclic molecule encased within the axial molecule, and end-capping material connected to both ends of the axial molecule. The side chains of the axial molecule contain a first functional group capable of forming hydrogen bonds; The side chains of the cyclic molecule contain a second functional group capable of forming hydrogen bonds; The quasi-rotaxane structural units form a three-dimensional supramolecular network through non-covalent bonds formed by the first functional group and / or the second functional group.

2. The quasi-rotaxane supramolecular network binder as described in claim 1, characterized in that: The axial molecule is a linear polymer, and the number-average molecular weight of the linear polymer is 50,000 to 500,000. And / or, the first functional group includes at least one of carboxyl, hydroxyl and amino groups; And / or, the axial molecule includes at least one selected from acrylic acid, sodium alginate, sodium carboxymethyl cellulose, guar gum, polyethylene glycol, polyvinyl alcohol, chitosan, polyvinylamine, polyallylamine, and gelatin.

3. The quasi-rotaxane supramolecular network binder as described in claim 1, characterized in that: The cyclic molecule includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, carboxycucurbita, and carboxy crown ether; And / or, the second functional group includes at least one of carboxyl and hydroxyl groups.

4. The quasi-rotaxane supramolecular network binder as described in claim 1, characterized in that: The quasi-rotaxane supramolecular network binder also includes divalent and higher-valent metal ions, which form ionic bonds with the first functional groups on the side chains of the axonal molecules to connect the axonal molecules of different quasi-rotaxane structural units; And / or, the end-capping material includes at least one of nano-silica, nano-diamond, dendritic macromolecules, fullerene, 2,4-dinitrofluorobenzene and protein; And / or, the molar ratio of the cyclic molecule to the axial molecule is 1:(10-100). And / or, the molar ratio of the end-capping material to the axial molecule is (1-3):

1.

5. A method for preparing a quasi-rotaxane supramolecular network binder as described in any one of claims 1 to 4, characterized in that, It includes: Dissolve the axial molecules in the first solvent to obtain an axial molecule solution; A cyclic molecule is added to the axial molecule solution to perform cyclization, thereby obtaining a quasi-rotaxane intermediate solution; An end-capping substance was added to the quasi-rotaxane intermediate solution to carry out an end-capping reaction, resulting in a reaction solution. The reaction solution was purified to obtain a quasi-rotaxane supramolecular network binder.

6. The method for preparing the quasi-rotaxane supramolecular network binder as described in claim 5, characterized in that: The end-capping reaction includes: stirring the reaction at 40–60°C for 12–24 hours; And / or, the piercing process includes: ultrasonication for 1 to 6 hours at a power of 100 to 300 W.

7. A silicon negative electrode sheet, characterized in that, It includes active substances, conductive agents, and quasi-rotaxane supramolecular network binders as described in any one of claims 1 to 4.

8. The silicon negative electrode sheet as described in claim 7, characterized in that: The mass ratio of the quasi-rotaxane supramolecular network binder, active material, and conductive agent is (5-15):(70-90):(5-15); And / or, the particle size of the active substance is 50-150 nm.

9. A method for preparing a silicon negative electrode sheet as described in claim 7 or 8, characterized in that, It includes: After mixing the quasi-rotaxane supramolecular network binder, active material and conductive agent, a second solvent is added to prepare a silicon anode slurry; The silicon anode slurry is coated onto the current collector and dried to obtain a silicon anode sheet.

10. A battery, characterized in that: It includes the silicon anode electrode as described in claim 7 or 8.